“…‘Who Do Men Say That I Am?’” – Mark 8:27 : Social construction and perceptions of disability in Singapore. - Puvana Devi Murugesan R. (2013)
This research aims to examine the social construction of disability, address the gap in the prevalent literature where individuals interpret, and examine social obstacles that people with disabilities face. I do this by re-examining what individuals identify as disability and how they construe the lived experiences of people with disabilities in Singapore. Drawing on in-depth interview data, I find that there is no dominant mode of perceiving disability among individuals. This implies that the concept of a homogenous ‘disabled community’ propagated by the Singapore government and media are not evenly received by the general public. Nevertheless, there is an agreement that there are social obstacles that limit the ability of people with disabilities to function effectively in society, and that these social barriers can be more disabling than individual impairments. There is also a call for a more barrier-free and gracious Singapore.